HUBUNGAN REGULASI DIRI DENGAN PERILAKU KONSUMSI ALKOHOL PADA EMERGING ADULTHOOD - Sofiah, Siti; Putri, Ellyana Ilsan Eka (FKDP (Forum Komunikasi Dosen Peneliti), 2024)
The modern era has brought about significant changes in all aspects of life. These changes have both positive and negative impacts, one of which is deviant behavior related to alcohol consumption. The research aims to understand the relationship between self-regulation and alcohol consumption behavior during emerging adulthood. The study involved 55 respondents in emerging adulthood. It utilized a quantitative approach with purposive sampling technique. Data analysis was conducted using the Pearson product-moment correlation test. The research results obtained a significance value of 0.001 (<0.05) with a correlation coefficient value of -0.422, indicating a correlation between self-regulation and alcohol consumption behavior during emerging adulthood. The findings suggest a relationship between self-regulation and a moderate influence on alcohol consumption behavior.